ANALISIS HUBUNGAN PELAYANAN DENGAN KEPUASAN PELANGGAN PADA BENGKEL CANDERA MOTOR DI KAUR UTARA KABUPATEN KAUR - -, Mitior; Susena, Karona Cahya (Ekombis Review, 2014)
Mitior, Karona Cahya Susena; An Analysis of the relationship between Services and the Customer Satisfaction At Motor Candera repair shop In Kaur regency. This research aimed to analyze the relationship between Services and the Customer Satisfaction At Motor Candera repair shop In Kaur regency. It used Spearman Rank and t test as the data analysis method. The result of the research showed that it has a correlation of 0,701 in spearman rank. It means that there is a high correlation between the services and the customer satisfaction in Candera Motor. The higher the service provided will increasingly the levels of satisfaction of the customer. The Hypothesis testing results showed that tcount is greater than ttable (7,482 > 1,672). Thus the hypothesis H0 is rejected and the Ha are received. It means that the services has a significant relationship with the customer satisfaction at Candera Motor repair shop in Kaur regency.